Negotiating the tropes of travel writing: William Dalrymple's From the Holy Mountain as a counter-narrative. Issue 4 (2nd October 2018) - George, Ajie
ABSTRACT: Contemporary travel writing reflects the changes that have occurred in the fields of literature, history, politics and cultural studies; developments in the genre have created the space for engagement with complex geopolitical issues and also for redefining some of its own conventions. William Dalrymple's From the Holy Mountain: A Journey in the Shadow of Byzantium (2004) traces and establishes the known, but often forgotten fact that Christianity is essentially an Eastern religion, even as it challenges the dominant contemporary discourses of difference between Christianity and Islam. While on the one hand it tries to discern areas of correspondence between the two religions, on the other, it counters popular travel theory which dismisses all travel writing as "colonial". In recording the subjective responses of the victims of physical and epistemic violence in West Asia, this article argues, Dalrymple makes innovative use of narrative strategies to present an ethically engaged account – a counter-narrative to dominant political and theoretical metanarratives.